Encouragement to Reading and Writing at Finca Guararí School: A Ludic and Creative Experience Within the Project “Setting up an Implementation Proposal of the Community Teachers Program” - Barberousse-Alfonso, Paulette (2019)
The main objective of this article is to present a pedagogical experience of encouragement to reading and writing, conducted by a group of university students enrolled in the Pedagogy program with emphasis on 1st and 2nd cycles, as part of the project Construyendo una propuesta de implementación del Programa Maestros Comunitarios of the División de Educación Básica (DEB) at the National University of Costa Rica (UNA). Even though this article is derived from an integrated project (Teaching-University Extension), the activities described point out qualitative teaching experiences both for the students at DEB-CIDE-UNA and for children at Finca Guararí School. The article includes a brief description of the Maestros Comunitarios Program developed both in Uruguay and the Costa Rican context of Guararí, Heredia (where the experience was developed). It also addresses some theoretical background related to the importance of reading and writing for the learning process, as well as the encouragement to reading and writing. Following an action-research methodological route, the experience was developed through activities and play strategies using puppets and puppet frame theaters designed for storytelling based on the strategies Gianni Rodari (1920-1980) created in his “Fantasy Grammar” (Rodari, 1973) proposal. The experience took place within Finca Guararí School in Heredia Province during the 1st school cycle 2017. A total of 60 children participated, as well as 23 university students from DEB-UNA. The analysis of results considered the experience as satisfactory since children enjoyed creating puppets while sharing quality time with their school peers. University students pointed out that children exhibited a “higher level” of performance compared to the “expected one.” However, they considered the short duration of the experience as a limitation. Most of the hosting school teachers said they had observed changes in motivation towards reading and more active participation of the children in classroom. The experience is considered useful from perspective of the formation of I and II cycle teachers for basic general education. In conclusion, encouragement to reading and writing is regarded as an important pedagogical strategy since it promotes learning and knowledge based on approaching written texts.